Performance Evaluation of Emulsion Liquid Membrane on Chlorpyrifos Pesticide Removal: Stability, Mass Transfer Coefficient, and Extraction Efficiency Studies - Al-Damluji, Farrah Emad; Mohammed, Ahmed A. (Engineering, Technology & Applied Science Research, 2023)
Emulsion Liquid Membrane (ELM) is an emerging technology that removes contaminants from water and industrial wastewater. This study investigated the stability and extraction efficiency of ELM for the removal of Chlorpyrifos Pesticide (CP) from wastewater. The stability was studied in terms of emulsion breakage. The proposed ELM included n-hexane as a diluent, span-80 as a surfactant, and hydrochloric acid (HCl) as a stripping agent. Parameters such as mixing speed, aqueous feed solution pH, internal-to-organic membrane volume ratio, and external-to-emulsion volume ratio were investigated. A minimum emulsion breakage of 0.66% coupled with a maximum chlorpyrifos extraction and stripping efficiency were achieved at 96.1% and 95.7% at best-operating conditions of 250/50 external-to-emulsion volume ratio, external feed solution pH 6, 250rpm mixing speed, and 1:1 internal-to-membrane volume ratio at 10min contact time without utilizing a carrier agent. A study of extraction kinetics and estimation of mass transfer coefficient was also conducted (3.89×10-9m/s). The results of this work can be extended to the removal of other types of pesticides from wastewater.